A comment on Dietmar Heidemann’s account on Kant’s Non-Conceptual Aesthetics: Against an active understanding - Schleich, Nora (Con-Textos Kantianos. International Journal of Philosophy, 2021)
This paper aims to contribute to an ongoing and controversial debate about non-conceptuality in Kantian aesthetics. It is a replica on a paper of Dietmar Heidemann in Con-Textos Kantianos N.° 12, to which I do consent, but I’d like to give some additional comments on a specific issue: I show in this paper that the problem about whether or not the understanding contributes to aesthetic judgment can be elucidated by means of a revaluation of the imagination’s capacity of formal representation and the subsuming activity of the power of reflective judgment. I argue that the understanding is considered by the power of reflective judgment merely in his lawfulness in order to find a universal under which the imagination’s particular, the formal representation of the beautiful shape, can be subsumed.